Exploring methods for assessing stakeholder perspectives in Scaling-Up Nutrition (SUN) countries: a scoping review - Adi Lukas Kurniawan; Olivinia Qonita Putri; Temidayo Akinreni (BMJ Open)
Objectives The scaling-up nutrition (SUN) initiative, which was launched in 2010 to eradicate malnutrition in all its forms by 2030, collaborates with a diverse range of stakeholders, such as governments, non-governmental organisations (NGOs), donors, businesses and academia. Given the widespread adoption of this multisectoral approach, it is crucial to explore methods for evaluating the perspectives of multiple stakeholders in child undernutrition topics.Design This scoping review was carried out following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews checklist.Data sources Six peer-reviewed databases, including PubMed, Web of Science, Cochrane, Embase, CINAHL and PROQUEST ASSIA, were systematically searched.Eligibility criteria Original English studies published between 1 January 2010 and 1 June 2023, focusing on undernutrition in SUN countries.Data extraction and synthesis Two reviewers independently screened titles, abstracts and full texts for inclusion and extracted data using Rayyan.Results Out of the 4533 articles, 19 met the inclusion criteria for the review, and 5 more were added through manual searches. These studies were conducted in 14 SUN countries, with 62% using mixed methods and the remaining using qualitative methods. Six methods were used to gather stakeholder perspectives, including in-depth interviews, focus group discussions, Net-Map, organisational network analysis and Q methodology. Most studies focused on government, development partners and NGOs, while only two studies involved the business network.Conclusions Our study indicates that study on stakeholder perspectives in SUN countries focuses mainly on those showing progress in malnutrition/undernutrition reduction. Future research should explore countries with less progress to improve partnership frameworks. The SUN movement should establish a standard method for evaluating stakeholder perspectives, considering both outcomes and processes.Trial registration number The final protocol was registered prospectively with the Open Science Framework in July 2023 (https://osf.io/te7cb).